Freedom to Learn in Ki Hajar Dewantara's Perspective: Historical Studies and Their Relevance to Character Education - Widiyarto, Sigit; Purnomo, Budi (IJBLE Scientific Publications Community Inc., 2023)
Ki Hajar Dewantara is an important figure in the history of Indonesian education. The ideas set forth in various writings are still relevant to the struggle for. The purpose of this study is to describe Ki Hajar Dewantara's perspective on independent learning and describe its relevance to student character education. The research method used is library research method. The results that independent learning is an educational idea based on independence in living one's life but must follow the prevailing norms. The learning carried out aims to improve cognitive abilities, understanding, and the ability to practice the information that has been learned. The concept of character education advances and changes the mind, body, and attitude (inner strength, character), virtuous, intelligent, intelligent and able-bodied individuals. His concepts and ideas can become the basis for the development of modern education that is able to teach students to master science so that they can elevate the dignity of students even higher, not the other way around and factual